Old but resilient story: Impact of decentralization on social welfare - José Luis Alberto Delgado; Dilek Demirbas; Ahmet Faruk Aysan (Journal of Risk and Financial Management, 2022)
This paper analyzes the fiscal performance of Turkey and Argentina during the period 2000-2021, when both countries faced rapid economic growth with the consequent impact on social welfare. This work explored two different systems: Centralization in Turkey and Federalism in Argentina and, in general, studied the decentralization impact of both the systems on social welfare. This study intended to create new social welfare indexes in other regions to analyze the resource allocation in different regions of these countries. As a first step, we built a regional human development index (HDI) for each region. This attempt is considered a new contribution to the literature and intended to fill the gap in this field. Afterward, this index was compared with the fiscal resources allocation (FRA), used as a proxy of fiscal decentralization in an econometric panel data model. By using this method, we concluded that the social welfare indexes have a positive relationship with the fiscal resource allocation in the Federal system, such as in Argentina, but not in the centralized system such as in Turkey during the period analyzed from 2000 to 2020.
Keywords: C43; D6; H3; H11; H21; 650; Turkey; Argentina; decentralization; fiscal centralization; HDI index